Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

ihatealgebrasomuch

  • 4 years ago

What would be the best way to solve 3d^2+6d-1=0

  • This Question is Closed
  1. jim_thompson5910
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Use the quadratic formula as it works with every quadratic (regardless of solution type) \[\Large d = \frac{-b\pm\sqrt{b^2-4ac}}{2a}\] \[\Large d = \frac{-(6)\pm\sqrt{(6)^2-4(3)(-1)}}{2(3)}\] \[\Large d = \frac{-6\pm\sqrt{36-(-12)}}{6}\] \[\Large d = \frac{-6\pm\sqrt{48}}{6}\] \[\Large d = \frac{-6+\sqrt{48}}{6} \ \text{or} \ d = \frac{-6-\sqrt{48}}{6}\] \[\Large d = \frac{-6+4\sqrt{3}}{6} \ \text{or} \ d = \frac{-6-4\sqrt{3}}{6}\] \[\Large d = \frac{-3+2\sqrt{3}}{3} \ \text{or} \ d = \frac{-3-2\sqrt{3}}{3}\] So the solutions are \[\Large d = \frac{-3+2\sqrt{3}}{3} \ \text{or} \ d = \frac{-3-2\sqrt{3}}{3}\]

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy